The Percentage of Speech “Error Analysis” of American President - Andi sadapotto; Sam Hermansyah; Muhammad Hanafi; Lababa Lababa; Syamsu T; Nurul Fadhilah Suardi; Ibrahim manda (Universitas Muhammadiyah Enrekang, 2021)
This research aims to analyze the kinds of error morphology in English speeches of American President and knowed the persentage of morphological errors in English Speeches of American President. As for the kinds of error morphology in English speeches of American President, the kinds are free morpheme, bound morpheme, affixes (prefix, suffix, and compound). This research design used is qualitative research. Qualitative research among others are descriptive, the data collected more in the form of words or pictures rather than numbers, The researcher chose qualitative case study research in descriptive qualitative because the data of this study described seeing the actual reality in the form of spoken language, and analyzed and interpreted with the objective to then described in the form of words and language. Qualitative descriptive method is a method that researchers can use to analyze by doing fact-finding with the right interpretation. Qualitative research is closely associated with the context. The result of this research showed that are in English Speeches of American President still found error morphology even thought they are narrative speakers. They made afix, prefix, suffix errors. Besides that, some of the president also made errors in free morpheme, bound morpheme, and compound.The researcher was founded 16 errors totally. In the case it consist of 18,75% errors in free morpheme 56,25% errors in bound morpheme, 25% in affixes there are 12,50% error in prefix, 6,25% errors in suffix , and 6,25% error in compound. Meanwhile, the dominant error in English Speeches of American President is bound morpheme which reaches 56,25 % from 16 or 100%.